Ergonomic Risk Analysis on Traditional Weaving Workers on Semau Island Kupang Regency - Ruliati, Luh Putu; Setyobudi, Agus; Talahatu, Anna Henny; Takaeb, Afrona Elisabeth Lelan (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Musculoskeletal disorder has caused casualty on traditional weaving workers. With manual equipment that uses no electricity, the workers do not apply anthropometry into their daily labor; resulting in working with bent position. Such condition forces the workers to be in a non-ergonomic work position. The research objective was to determine the relationship between work fatigue, workload, and work attitude with musculoskeletal disorders in traditional weaving workers. This research is an analytic descriptive research with a cross sectional study design. The sample in this study was 38 traditional weavers. The results showed that there was a relationship between work fatigue, workload, and work attitude with musculoskeletal disorders in traditional weaving workers on Semau Island, Kupang Regency with p-value <0.05. Workers can be given counseling and pamphlets regarding ergonomic and comfortable work, so as to avoid occupational safety and health problems.